The Use of Board Games and Digital Games Preschoolers: Results of a Survey of Russian Parents - Y.A. Tokarchuk; O.V. Salomatova; E.V. Gavrilova (Психолого-педагогические исследования, 2024)
The article presents the results of an empirical study conducted within “The Influence of Digital Activity on the Development of Cognitive Functions in Preschool Age” project. In order to compare the data on the use of board games and digital games, a special “Contemporary Children: Digital Games vs. Board Games” questionnaire was developed (O.V. Salomatova, Yu.A. Tokarchuk, 2023), intended for the parents of preschoolers. The survey was conducted from March to September 2023 and involved parents of children aged 3 to 7 years old (N=556). It was shown that parents consider board games to be a more preferable pastime for children than digital games. According to the survey, board games in most cases involve the presence of a gaming partner, while digital games are more often an individual activity. In comparison with board games, parents more frequently use digital applications as a means of monitoring their child's behavior or as a method of reward. At the same time, according to the survey, parents less often actively participate in the process of digital gaming, allowing children to play independently or under their supervision. Board games more frequently involve parents in the gaming process.